Hubungan Anemia Dalam Kehamilan Dengan Kejadian Bayi Berat Badan Lahir Rendah BBLR Di RSUD Kabupaten Tangerang - Rini Handayani; Nurry Ayuningtyas Kusumastuti; Nuryanti Nuryanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Babies with Low Birth Weight (LBW) are a health problem for babies and can affect the number of Infant Mortality Rates (IMR). Another factor that can cause LBW is the hemoglobin level of pregnant women or anemia in pregnant women. Anemia in pregnant women can cause mortality and morbidity in both mother and baby. Research objective: to determine the relationship between anemia in pregnancy and the incidence of LBW babies in RSUD Kabupaten Tangerang. Research method: this study used an analytic observational design with a retrospective cross-sectional approach. The sample for this study were all babies born with a birth weight < 2500 grams for the September-December 2022 period of 123 babies. The sampling method used in this study is the total sampling method. Data was obtained by filling out a note sheet from the search results of the respondent's medical records. Univariate and bivariate data analysis using the chi-square test. The results of the study: of the 123 respondents, the majority were 75 respondents (61%) with mild anemia and 97 respondents (61%) with LBW. There was a relationship between anemia in pregnancy and the incidence of LBW babies with a p value of 0.000 <α (0.05). Conclusions and suggestions: There was a relationship between anemia in pregnancy and the incidence of LBW babies in RSUD Kabupaten Tangerang. Hospitals are advised to improve nursing services, especially health education to increase pregnant women's knowledge about the importance of iron during pregnancy in an effort to prevent anemia during pregnancy, one of which can cause low birth weight babies.